17p11.2 Deletion In A Dysmorphic Girl With Phenotipic Evidence Of Smith-Magenis Syndrome And A Literature Review - Talavera-Vargas-Machuca, Sergio (2016)
Chromosomal deletions are structural abnormalities that cause loss of genomic material, depending on itslength they use to generate several disabling genetic conditions. Interstitial deletion of chromosome 17 shortarm in 17p11.2 region is related to the appearance of phenotypic characteristics related to a genetic conditionknown as Smith-Magenis syndrome. This deletions spans in a range between <1.5 and 9 Mb, shows somefeatures as craniofacial dysmorphia, delayed psychomotor development, speech problems, sleep disorders,limb abnormalities, malformations of brain, heart and kidney also are expressed. We present a case of a 10monthsold girl with brachycephaly, bulging forehead, sunken eyes, epicanthal folds, malformed ears, shortphiltrum, small mouth and ventriculomegaly. The gir´sl karyotype was 46,XX,del(17)(p11.2), no moleculartests were performed because they were not available, but the phenotypic evidence, the clinical and classicalcytogenetic aspects are suggestives of Smith-Magenis Syndrome. We propose to follow up of this case andperform modern molecular tests for a definitive diagnosis.